A new species of the caridean shrimp genus Lebbeus White, 1847 (Crustacea: Decapoda: Thoridae) from the southwestern Sea of Okhotsk, Hokkaido, Japan - Matsuzaki, Koji; Hibino, Mai; Komai, Tomoyuki (Zootaxa, 2015)
A new species of the caridean shrimp genus Lebbeus White, 1847 (Thoridae), L. fujimotoi n. sp. is described and illustrated on the basis of material from the Nemuro Strait, southwestern part of the Sea of Okhotsk, Hokkaido, Japan, at depths of 500–800 m. The new species belongs in the informal species group characterized by the possession of an epipod only on the third maxilliped, containing only L. elegans Komai, Kohtsuka & Hayashi, 2004 among the 65 previously described specific taxa. The elongate and strongly upturned rostrum with more numerous ventral teeth (seven or eight versus one to four) and the presence of a posteroventral tooth on the fourth pleonal pleuron immediately distinguish the new species from L. elegans. Species of Lebbeus reported from the Sea of Okhotsk are briefly overviewed.